2003
DOI: 10.1016/s0886-3350(03)00667-9
|View full text |Cite
|
Sign up to set email alerts
|

Subjective and objective measurement of human accommodative amplitude

Abstract: Subjective measures of accommodation tend to overestimate true accommodative amplitude. Methods exist to measure accommodation objectively. These include stimulating accommodation with trial lenses or pilocarpine 6% and measuring the accommodative response with an objective optometer such as a Hartinger coincidence refractometer. Objective measures of accommodation should be used to determine whether accommodation can be restored in presbyopes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
88
1
3

Year Published

2007
2007
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 114 publications
(99 citation statements)
references
References 38 publications
7
88
1
3
Order By: Relevance
“…23 Duane's results have been slightly modified because his data were referred to the spectacle plane (placed 12 mm in front of the eye) and reduced by 20% due to the overestimated values yielded by the push-up method relative to those yielded by the minus-lenses method. 24 Figures 2 and 3 indicate that the subjective data collected by two independent methods are internally consistent and in broad agreement with published norms for the human eye. Figure 4 shows an example of the accommodation response curves for each of the 32 metrics, for a 23-year-old subject.…”
Section: Amplitude Of Accommodation Minus Lenses (D) Amplitude Of Accsupporting
confidence: 79%
See 1 more Smart Citation
“…23 Duane's results have been slightly modified because his data were referred to the spectacle plane (placed 12 mm in front of the eye) and reduced by 20% due to the overestimated values yielded by the push-up method relative to those yielded by the minus-lenses method. 24 Figures 2 and 3 indicate that the subjective data collected by two independent methods are internally consistent and in broad agreement with published norms for the human eye. Figure 4 shows an example of the accommodation response curves for each of the 32 metrics, for a 23-year-old subject.…”
Section: Amplitude Of Accommodation Minus Lenses (D) Amplitude Of Accsupporting
confidence: 79%
“…Although a subjective test provides important information about near visual ability, it does not accurately measure the accommodative optical change that occurs in the eye. This is because the eye's depth-of-field causes subjective measurements to overestimate the objectively measured accommodative amplitude 4,5 unencumbered by depth-of-field effects. For example, open-field-of-view autorefractors [6][7][8][9] are commonly used to obtain accurate, objective measurements of accommodation.…”
Section: Introductionmentioning
confidence: 99%
“…[6][7][8][9][10][11][12] Keep in mind that the normal range usually applied was obtained from the method of calculation of Donders in emmetropic subjects, if these values are compared with ametropic subjects to determine if the amplitude of accommodation that is obtained is normal, you should perform the calculation considering the effect of neutralizing lens (Am eye ).…”
Section: Discussionmentioning
confidence: 99%
“…Several pilot studies have been done to determine the value of the amplitude of accommodation by different methods, and found that the values obtained by the push-up method provided higher values than other methods. [6][7][8][9][10][11][12] It is therefore important to evaluate how precise in the subjective measurement of the amplitude of accommodation and, if necessary, refine it.…”
mentioning
confidence: 99%
“…For instance, accommodation can be tested with a number of techniques [48], and participants reported using several different methods. Our finding that the optometrists did not reach agreement on specific oculomotor and BV testing methods does not detract from the importance of conducting the testing in mTBI.…”
Section: Examination Procedures Testmentioning
confidence: 99%